Community‐Driven Research Agenda to Reduce Health Disparities. Issue 6 (17th November 2015) - McElfish, Pearl A.; Kohler, Peter; Smith, Chris; Warmack, Scott; Buron, Bill; Hudson, Jonell; Bridges, Melissa; Purvis, Rachel; Rubon‐Chutaro, Jellesen
Abstract: This paper describes how a new regional campus of an academic health center engaged in a community‐based participatory research (CBPR) process to set a community‐driven research agenda to address health disparities. The campus is situated among growing Marshallese and Hispanic populations that face significant health disparities. In 2013, with support from the Translational Research Institute, the University of Arkansas for Medical Sciences Northwest began building its research capacity in the region with the goal of developing a community‐driven research agenda for the campus. While many researchers engage in some form of community‐engaged research, using a CBPR process to set the research agenda for an entire campus is unique. Utilizing multiple levels of engagement, three research areas were chosen by the community: (1) chronic disease management and prevention; (2) obesity and physical activity; and (3) access to culturally appropriate healthcare. In only 18 months, the CBPR collaboration had dramatic results. Ten grants and five scholarly articles were collaboratively written and 25 community publications and presentations were disseminated. Nine research projects and health programs were initiated. In addition, many interprofessional educational and service learning objectives were aligned with the community‐driven agenda resulting in practical action to address the needs identified.